An investigation into twentieth century flute trios with special reference to representative works by Goossens, Sil'vansky, Raphael, Damase, Marx and Crumb - Heunis, Daniela (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1994)
This thesis ventures into the world of twentieth century chamber music, specifically the trios written for flute, cello and piano. The first chapter discusses the history of the trio, tracing its development from the trio sonata of the Baroque Period to the accompanied sonatas and specifically the sonatas with flute and cello obbligato. Following the unpopularity of the genre throughout the Romantic period, its greater prominence in the Twentieth century is discussed, mentioning specific groups through whom the repertoire has been extended. Forty trios are grouped according to compositional styles. Six trios, each representing an example of a specific style period, have been selected for more detailed discussion, with particular reference to the various ways in which a sense of unity is achieved in each trio. The English composer Eugene Goossens uses impressionistic images, whole tone and chromatic scale patterns and other motifs to unify his trio: "Five Impressions of a Holiday". Nikolay Iosifovich Sil'vansky's "The Hedgehog and the Nightingale" is based on a Russian tale by Juri Jarmicha and uses a narrator. The three characters are represented by specific motivic and / or thematic material which is used throughout the trio. Günter Raphael's Trio-Suite op 44 is the only cyclic work unifying the two outer movements, without repeating any additional motivic material. Jean-Michel Damase condenses some of the material introduced in the opening Prelude in both the two Largo's and the two Arias in his "Sonate en Concert" of 1950. Karl Julius Marx builds his entire "Trio op 61" on a flexible six-note motif. Various movements in the trio" Vox Ba1aenae" by the American George Crumb are 1inked through the use of motives and characteristic instrumental colour. A comprehensive list of 180 twentieth century trios has been compiled, including details of dedications, commissions and first performances. 163 composers from twenty countries, are represented.
Keywords: Goossens, Eugene, 1893-1962; SilÊ¹vanskÃÃ, NikolaÌŒi Iosifovich, 1915-1985; Raphael, Günter, 1903-1960; Damase, Jean-Michel, 1928-; Crumb, George; Woodwind trios (Flutes (3))